Evaluation of thrust force in drilling of woven kenaf fiber reinforced epoxy composite laminates - Mokhtar, Suhaily; Che Haron, Che Hassan; A. Ghani, Jaharah; Harun, Azmi (Institut Pengurusan Penyelidikan (RMI), Universiti Teknologi MARA, 2017)
Drilling or creating holes in composite parts are a necessary and sensible task, preponderantly for facilitating the assembly of joints. Within the present investigation, the drilling operation of natural fiber reinforced thermosetting (epoxy) composite laminates was assessed in terms of the drilling force. This study conjointly incorporated the employment of a Box Behnken Design with 17 test runs within which machining parameters corresponding to the cutting speed (20 – 70 m/min), feed rate (0.1 – 0.3 mm/rev) and drill sizes (6,9 and 12 mm) were taken as input variables. The consequences of two different types of tool materials (non-coated HSS and non-coated carbide) were conjointly evaluated within the study. The Response Surface Methodology (RSM) was used to analyze the thrust force when drilling woven kenaf fiber reinforced composites with non-coated HSS and non-coated carbide drill bits. Based on the study, the drill size and feed rate were found to be the most significant factors that influenced the thrust force in both of the cutting tool materials used in the study. In addition, the non-coated carbide drill bit shows a better performance of producing minimal thrust force values during the drilling of woven kenaf fiber reinforced composite laminates.